PENGUATAN KAPASITAS SUMBER DAYA MANUSIA DALAM MENINGKATKAN DAYA SAING PRODUK INDUSTRI PARIWISATA UNTUK MENGHADAPI ASEAN ECONOMIC COMMUNITY (AEC) DI DESA PELAGA KABUPATEN BADUNG - Suwena, I.K.; Widyatmaja, I.G.N.; Astina, I.B.K.; Pertiwi, P.R.; Sutaguna, N.T. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
Community service which carried out in Pelaga village, Petang, Badung aims to provide a wide space for local people to organizes and improves the system of management of eco tourism and to increases the participation of local communities in tourism development in Pelaga village through the well – packaging of eco tourism. In order to increase the income of local communities in Pelaga village, it is important to held this community empowerment through the utilization of its potencies, and then package it, as a valuable tourism product as well as to improve the finance and the power sources of those communities, also as a support of the tourism development in Badung. The targets of the activities of community service are the ecotourism manager and the young generations of Pelaga village. The approaching models are: 1. Participatory Rural Appraisal (PRA) Model, (2) Entrepreneurship Capacity Building (ECB) Model, (3) Knowledge/Technology Transfer Model. Some activities have been done in KKN – PPM program in Pelaga village, in order to address the various problems of eco – tourism faced by the local communities of Pelaga village, such as: Setting – up a sort of a foundation to manage the eco – tourism in Pelaga village, tour guide training for the local communities, packaging training in how to package the coffee processed products into tourism products, English for tourism courses, and provide the local communities houses as home stays for the tourists